The Predictive Role of Academic Hope in Academic Procrastination Among Students: a Mixed Methods Study - Dami, Zummy Anselmus; Tameon, Sance Mariana; Saudale, Jeheskial (Pedagogika, 2020)
The aim of the current study was to investigate the correlation of academic hope with academic procrastination; to determine the differences in the academic procrastination of both men and women; to understand why students conduct academic procrastination; and to know the academic hope of students. The study uses a mixed-method research design. The results showed that academic hope has a positive and significant correlation with academic procrastination; there is no significant difference between male and female students in any scale of academic hope and academic procrastination; the reason students conduct procrastination is “I generally delay before starting on work I have to do”; and the academic hope students are unique because it relates to God and parents.